Cost-effective groundwater control during excavation of subsea rock cavern - Lu, Ming (2014)
Groundwater seepage related problems are often the No.1 geological hazard in terms of construction expense and safety for subsea rock caverns. In order to excavate caverns safely and effectively, water control should be successfully addressed. Successful water control depends on a set of effective measures, from establishing hydro-geological model to grouting strategy and grout property improvement. In this paper, the authors try to propose a systematic water control methodology during excavation of subsea rock caverns. A reliable hydro-geological model building is the critical step to assess the seepage in the field. Traditional hydro-geological models are often not reliable due to its simplistic assumptions and lack of effective use of measurement data, and the calculated results do not provide useful prediction to guide the cavern design and excavation. To overcome these drawbacks, the information from the geological investigation data, aided by the artificial intelligence method, is used to establish the preliminary hydro-geological model. Based on site monitoring data and geological conditions, an innovation modeling method, back-analysis of the coefficient of hydraulic conductivity of the rock mass, can be used to calibrate the preliminary model. On the basis of established hydro-geological model, groundwater control during excavation mainly relies on accurate water bearing zones detecting ahead of the face, followed by pre-grouting. Two methods are commonly used to detect the water bearing zones: probehole method and geo-physical method. Both methods have their advantages and constraints. An advanced water bearing zone detecting method by integrating probehole method and geo-physical method is proposed. Once water bearing zones are detected, groundwater control is mainly achieved by pre-grouting. Sometimes, pre-grouting quality is not satisfactory due to the unreasonable grouting strategy and unsatisfied property of the grout. According to statistical analysis and comparison of successful grouting cases with similar conditions and relevant literatures, optimized pre-grouting strategy will be proposed, including grouting method selection and workflow determination. For better grouting quality, improvement of property of grout is necessary. To take influences of saline groundwater into account, improvement of grout (especially the rheological behavior) will be mainly achieved by laboratory tests and in-site trials. Based on systematic water management optimization, water control would be more cost-effective.